Compensation for the material damage in our industrial property law - Spajić, Bojana (Glasnik Advokatske komore Vojvodine, 2020)
In the era of the digital revolution and the global market economy, the economic interests of holders of industrial property rights face threats from new and advanced forms of infringement. In order to guarantee the safeguarding of the material status of the rightholders, standards of protection have been set at the international level as well as within the European Union – with harmonization expected to take place on a global scale. These standards, related to compensation for material damage due to the infringement of industrial property rights, largely deviate from the general rules on compensation for damage. The reason for deviations lies in the specifics of the authorities that are inherent to these rights and the intangible nature of the intellectual property that is the subject of the protection: hence the need for specific methods devised to calculate the amount of damages caused by infringement of industrial property rights. This paper analyses special rules on compensation for material damage caused by infringement of industrial property rights, observed in domestic law as it has developed from 1995 and onwards. The subject of the analysis are the relics of previous positive law, i.e. triple compensation, and compensation of up to three times the amount of the license fee, as well as the current regulations on the damages set as a lump sum compensation under which it may not be less than the compensation for legal use of the object of protection and compensation equal to the infringer’s profit. The aim of this paper is to propose de lege ferenda norms for an enhanced regulation of the matter of compensation for material damage in the field of industrial property.